Driving toward Modernity : Cars and the Lives of the Middle Class in Contemporary China - Zhang, Jun, 1977- (Book collections on Project MUSE., 2019)
"This book explores, ethnographically, the entanglement between the rise of the automotive regime and emergence of the middle class in South China, through which a nuanced picture of China's great transformations is depicted"--